PSII-33 Differences in prostaglandin release in cows with high vs low circulating concentrations of pregnancy associated glycoproteins. (5th December 2019) - Reese, Sydney T; Schubach, Kelsey; Brandão, Alice; West, Sarah M; O'Neil, Meaghan M; Cardoso, Rodolfo C; Williams, Gary L; Pohler, Ky
Abstract: Embryonic mortality (EM) is a major factor limiting pregnancy rates in cattle and occurs early (< day 28) or late (≥ day 28) during gestation. However, causes and mechanisms associated with late EM remain unknown. Despite negative connotations related to pregnancy, prostaglandin F2α (PGF) is capable of being released by the bovine uterus between days 28 and 32 of gestation. Therefore, the objective was to evaluate differences in PGF release between cows with high circulating concentrations of pregnancy associated glycoproteins (PAG) vs low PAG following an oxytocin (OT) challenge. Increased concentrations of PAG are associated with pregnancy success. At day 29 of gestation, pregnant cows were divided into high (n = 10) and low (n = 10) PAG groups and received either 100 I. U. of oxytocin intramuscularly (OT) or saline (control). Blood samples were collected every 30 minutes beginning 1 hour before and continuing for 4 hours after treatment. Prostaglandin F2α metabolite (PGFM), progesterone (P4 ), estradiol (E2 ) and PAG concentrations were determined. Peak concentration of PGFM occurred 2 hours after OT injection (average high PAG group peak: 345.6 ± 73.6 pg/mL; low PAG group peak: 326.4 ± 61.4 pg/mL, P > 0.05) and returned to baseline levels by 4 hours. No correlations were observed between PAG and PGFM concentrations (P > 0.05). There was no difference in initial or final PGFM concentrations between high or low PAG groups and control animals (P > 0.05). Furthermore, there was no difference in P4 or E2 concentration between treatment and control animals (P > 0.05) despite a luteolytic release of PGF2α . In summary, cows with high vs low PAG concentrations at day 30 of gestation have a similar PGFM response to OT challenge. This project supported by Agriculture and Food Research Initiative Competitive Grant no. 2017-67015-26457 from USDA-NIFA.